Characteristics of new Mg0.5(Zr1-Sn )2(PO4)3 NASICON structured compound as solid electrolytes - Mazni, Mustafa; Mohd Saiful Asmal, Rani; S.B.R.S., Adnan; F.M., Salleh; N.S., Mohamed (Elsevier, 2020)
Mg0.5(Zr1-xSnx)2(PO4)3 with 0.0 ≤ x ≤ 1.0 compounds were synthesized using water-based citrate sol-gel method. X-ray diffraction and its Rietveld refinement analysis for x ≤ 0.6 confirmed the formation of a monoclinic NASICON structured compound with a space group P21/n upon sintering at 800 °C for 24 h. The total conductivity value obtained for Mg0.5ZrSn(PO4)3 is 2.47 × 10-5 S cm-1 at 500 °C which is two order of magnitude higher compared to the pristine Mg0.5Zr2(PO4)3. The activation energy value for pristine Mg0.5Zr2(PO4)3 and Mg0.5ZrSn(PO4)3 are Ea = 0.84 ± 0.05 eV and Ea = 0.79 ± 0.04 eV respectively. Furthermore, exponent s(T) behaviour was found to increase with rising temperature and is in good agreement with the correlated barrier hopping model. It seems that Mg0.5ZrSn(PO4)3 achieved higher conductivity and lower activation energy than the pristine Mg0.5Zr2(PO4)3, indicates that the Sn4+ ion substituted compound make a desirable solid electrolytes for magnesium power storage.